GEN Z IN TRANSITION: BETWEEN IDEALISM AND PRAGMATISM IN POLITICS - Salsabila, Sally; Chaniago, Dwi Setiawan; Hilmi, Farida (Journal of Social Politics and Governance (JSPG), 2025)
The 2024 general election positions Generation Z as a major electoral bloc (33.6% of voters), yet their engagement is often perceived as apathetic. This study examines the motivations of Gen Z’s political participation and their relationship with participation typologies. A mixed-methods convergent design was applied, involving 200 Mataram University students. Quantitative data from questionnaires were analyzed using cross-tabulations, chi-square tests, and ordinal logistic regression, while qualitative data from open responses were thematically coded. Findings show that most respondents were spectators (57%), followed by critics (22%), gladiators (11.5%), and apathetic (9.5%). Idealistic motives (especially voice matters, policy change, and political education) were dominant. Chi-square tests revealed significant links between several idealistic factors and active participation, but in regression only political identity (B = –1.356, p = .005) consistently predicted critic and gladiator roles. Pragmatic motives (e.g., economic reward, mobilization) appear in narratives but lose significance in multivariate tests, indicating their role as situational triggers rather than structural drivers. These results highlight a paradox: Gen Z’s participation is grounded in idealism yet negotiated within pragmatic realities. Politics for Gen Z thus emerges not merely as transactional, but as a space for identity, learning, and normative aspirations.